Association between sleep quality and quality of life in nursing professionals working rotating shifts - Palhares, Valéria de Castilho [UNESP]; Corrente, José Eduardo [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Revista De Saude Publica, 2014)
Objective: To analyze the association between sleep quality and quality of life of nursing professionals according to their work schedules. Methods: A prospective, cross-sectional, observational study was conducted between January and December 2010, with 264 nursing professionals, drawn from 989 subjects at Botucatu General Hospital and stratified by professional category. The Pittsburg Sleep Quality Index and the WHOQOL-bref were administered to evaluate sleep quality and quality of life, respectively. Self-reported demographic data were collected with a standard form. Continuous variables were reported as means and standard deviations, and categorical variables were expressed as proportions. Associations were evaluated using Spearman's correlation coefficient. The association of night-shift work and gender with sleep disturbance was evaluated by logistic regression analysis using a model adjusted for age and considering sleep disturbance the dependent variable. The level of significance was p < 0.05. Results: Night-shift work was associated with severe worsening of at least one component of sleep quality in the model adjusted for age (OR = 1.91; 95% CI 1.04; 3.50; p = 0.036). Female gender was associated with sleep disturbance (OR = 3.40; 95% CI 1.37; 8.40; p = 0.008). Quality of life and quality of sleep were closely correlated (R = -0.56; p < 0.001). Conclusions: Characteristics of the nursing profession affect sleep quality and quality of life, and these two variables are associated.

Objetivo: Analisar a associação entre a qualidade do sono e a qualidade de vida dos profissionais de enfermagem segundo organização do trabalho. Métodos: Estudo transversal, observacional e prospectivo, com 264 profissionais de enfermagem em Botucatu, SP, entre janeiro e dezembro de 2010. Os sujeitos foram sorteados entre os 989 indivíduos que trabalhavam no Hospital Geral de Botucatu e estratificados por categoria profissional. O Índice de Qualidade de Sono de Pittsburgh e o WHOQOL-bref foram aplicados para avaliar qualidade do sono e qualidade de vida, respectivamente. Os dados demográficos foram coletados por meio de formulário padrão. Variáveis contínuas foram apresentadas como média e desvio padrão e variáveis categóricas, como proporções. As associações foram avaliadas por meio do coeficiente de correlação de Spearman. As associações entre turno e sexo com a qualidade do sono foram analisadas por meio de regressão logística, no modelo corrigido para idade. Distúrbio do sono foi a variável dependente. O nível de significância adotado foi p < 0,05. Resultados: Trabalho noturno foi associado com prejuízo importante de pelo menos um componente da qualidade do sono (OR = 1,91; IC95% 1,04;3,50, p = 0,036). O prejuízo da qualidade do sono também se associou com o sexo feminino (OR = 3,40; IC95% 1,37;8,40; p = 0,008). Houve correlação estreita entre a qualidade de vida e qualidade do sono (r = -0,56, p < 0,001). Conclusões: Características próprias da profissão de enfermagem podem afetar a qualidade do sono e a qualidade de vida, e essas duas variáveis estão associadas entre si.
Associação entre qualidade do sono e qualidade de vida de profissionais de enfermagem que trabalham em turnos
Keywords: Nursing, team; Sleep; Sleep deprivation, epidemiology; Quality of life; Shift work; Cross-sectional studies; Equipe de enfermagem; Sono; Privação do sono, epidemiologia; Qualidade de vida; Trabalho em turnos; Estudos transversais